Structural Study of the Photo-Mediated Growth of Silver Nanoprisms - Matti Knaapila; Ulla Vainio; Sophie E. Canton; Gunnel Karlsson (Molecules, 2020)
We present a small-angle X-ray scattering (SAXS) study of the anisotropic photoinduced growth of silver (Ag) nanoprisms in aqueous dispersions. The growth of nearly spherical (<10 nm) Ag particles into large (>40 nm) and thin (<10 nm) triangular nanoprisms induced by 550 nm laser is followed in terms of particle size using indirect and direct methods for irradiation times up to 150 min. During the process, the surface-to-volume ratio of the particles decreased. The SAXS data of the initial solution fit well to the model of polydisperse spheres with pronounced average diameters around 7.4 nm and 10 nm. The data after 45 min irradiation fit well to the model containing approximately the same amount of the initial particles and the end product, the nanoprisms.